Immunotherapy for non-small cell lung cancer (NSCLC), as a stand-alone and in combination therapy. (August 2021) - Kaur, Jasmine; Elms, Jackson; Munn, Alan L.; Good, David; Wei, Ming Q.
Graphical abstract: Highlights: Non-small cell lung cancer causes over a million deaths worldwide each year. Traditional treatment modalities for NSCLC are unsatisfactory. Of all the approaches to treatment, cancer immunotherapy is the most promising. Cancer vaccine strategies have shown efficacy in treating NSCLC in clinical trials. The future of NSCLC treatment is combination immunotherapies and cancer vaccines. Abstract: Non-small cell lung cancer (NSCLC) is of major concern for society as it is associated with high mortality and is one of the most commonly occurring of all cancers. Due to the number of mutational variants and general heterogeneity of this type of cancer, treatment using conventional modalities has been challenging. Therefore, it is important to have improved therapeutic treatments like immunotherapy, that can specifically treat the disease while causing minimal damage to healthy tissue and additionally provide systemic immunity. Cancer vaccines are an important element of cancer immunotherapy and have been approved for treatment of a limited number of cancers, including NSCLC. This article highlights scientific evidence for several therapeutic treatment strategies for NSCLC, alone or in combination, which offers new hope for those suffering. Although cancer vaccines have had some success as a monotherapy, their potential in a combination therapy needs to be critically analyzed for future applications.